Thoracolumbar Rotation During Tai Chi Movements—A Biomechanical Analysis of the Entire Peking Style Routine - Wehner, Christian; Wehner, Carina; Schwameder, Hermann; Schobersberger, Wolfgang (Frontiers in Sports and Active Living, 2022)
The impact of spinal mobility and sagittal spinal shape on the development of balance impairment supports the hypothesis that enhancing spine flexibility results in an improvement in postural balance ability. Therefore, the aim of this study was to investigate whether the range of motion of thoracolumbar rotation during the movements of the Tai Chi Peking style routine is sufficient to improve thoracolumbar flexibility. Three-dimensional kinematic and kinetic data were collected from eight athletes of the German Wushu Federation, while performing all movements of the entire Peking style routine 1) in a competition version corresponding to national/international championships and 2) in a health sport version performed with shorter and higher stances. For each movement the total mean and standard deviation values for the total range of motion of thoracolumbar rotation was calculated. Statistical analysis was performed with the Wilcoxon signed-rank test for paired differences. Eight movements showed notable differences between the two versions. For the remaining movements, only minor differences were observed. All movements performed on both sides showed no significant lateral differences. Most of the Tai Chi movements cover a range of motion of thoracolumbar rotation sufficient for improving thoracolumbal spine flexibility, regardless of the performed version.